Retaliation - Mojtaba Taghizadeh (آموزه‌‌های فقه مدني, 2008)
Retaliation is a religious way for gaining the right and this way is legitimate by reliable reasons. Since the courts may also in some claims face with this problem and in accordance to the Article 167 of constitution must decide upon the regulations and principles in regard to the religious texts, considering and studding of this subject becomes necessary. Some may disagree with the retaliation because they worry about chaos in society, so they say that when the authority of a just judge is very extensive, there is no place for it. But the writer disagrees with this idea. It will be clear in this paper that upon the legal and traditional background of retaliation as well as the circumstances of the society and public order, the opportunity of vindication of rights can be bring about.